Human Cancer Cell Radiation Response Investigated through Topological Analysis of 2D Cell Networks - Luca Tirinato; Valentina Onesto; Daniel Garcia-Calderon; Francesca Pagliari; Maria-Francesca Spadea; Joao Seco; Francesco Gentile (Annals of Biomedical Engineering, 2023)
Clonogenic assays are routinely used to evaluate the response of cancer cells to external radiation fields, assess their radioresistance and radiosensitivity, estimate the performance of radiotherapy. However, classic clonogenic tests focus on the number of colonies forming on a substrate upon exposure to ionizing radiation, and disregard other important characteristics of cells such their ability to generate structures with a certain shape. The radioresistance and radiosensitivity of cancer cells may depend less on the number of cells in a colony and more on the way cells interact to form complex networks. In this study, we have examined whether the topology of 2D cancer-cell graphs is influenced by ionizing radiation. We subjected different cancer cell lines, i.e. H4 epithelial neuroglioma cells, H460 lung cancer cells, PC3 bone metastasis of grade IV of prostate cancer and T24 urinary bladder cancer cells, cultured on planar surfaces, to increasing photon radiation levels up to 6 Gy. Fluorescence images of samples were then processed to determine the topological parameters of the cell-graphs developing over time. We found that the larger the dose, the less uniform the distribution of cells on the substrate—evidenced by high values of small-world coefficient ( cc ), high values of clustering coefficient ( cc ), and small values of characteristic path length ( cpl ). For all considered cell lines, $$sw>1$$ s w > 1 for doses higher or equal to 4 Gy, while the sensitivity to the dose varied for different cell lines: T24 cells seem more distinctly affected by the radiation, followed by the H4, H460 and PC3 cells. Results of the work reinforce the view that the characteristics of cancer cells and their response to radiotherapy can be determined by examining their collective behavior—encoded in a few topological parameters—as an alternative to classical clonogenic assays.

A Review on Advances in Intra-operative Imaging for Surgery and Therapy: Imagining the Operating Room of the Future - Paolo Zaffino; Sara Moccia; Elena De Momi; Maria Francesca Spadea (Annals of Biomedical Engineering, 2020)

Longitudinal Motion Assessment of the Carotid Artery Using Speckle Tracking and Scale-Invariant Feature Transform - Salvatore Scaramuzzino; Claudio Carallo; Giampaolo Pileggi; Agostino Gnasso; Maria Francesca Spadea (Annals of Biomedical Engineering, 2017)

Motion Compensation in Hand-held Laser Scanning for Surface Modeling in Plastic and Reconstructive Surgery - Paolo Patete; Marco Riboldi; Maria Francesca Spadea; Giuseppe Catanuto; Andrea Spano; Maurizio Nava; Guido Baroni (Annals of Biomedical Engineering, 2009)